Capecitabine-associated coronary vasospasm: a case report. Issue 5 (23rd April 2008) - Papadopoulos, C A; Wilson, H
Abstract : Capecitabine (Xeloda) is an oral 5-fluorouracil pro-drug used in the treatment of two of the commonest cancers: breast and colorectal. This report concerns a 43-year-old woman with metastatic cancer of the sigmoid colon who developed cardiac chest pain 5 days after starting capecitabine therapy. Capecitabine-induced cardiac symptoms have previously been reported but infrequently. In the main they have documented pain and electrocardiogram (ECG) changes associated with exercise. This case report is of a patient with minimal cardiac risk factors, who had ischaemic cardiac pain with widespread ECG changes at rest that resolved with a nitrate infusion. Coronary vasospasm is proposed as the probable mechanism for the cardiac ischaemia and dramatic ECG changes. Capecitabine is now in widespread use and so physicians will encounter an increasing number of patients using this therapy. In the light of this, it is important that doctors in emergency and acute medicine are aware of its treatable cardiac side effects.